2016
DOI: 10.1038/srep18673
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and atenolol enhance metformin activity against breast cancer by targeting both neoplastic and microenvironment cells

Abstract: Metformin can induce breast cancer (BC) cell apoptosis and reduce BC local and metastatic growth in preclinical models. Since Metformin is frequently used along with Aspirin or beta-blockers, we investigated the effect of Metformin, Aspirin and the beta-blocker Atenolol in several BC models. In vitro, Aspirin synergized with Metformin in inducing apoptosis of triple negative and endocrine-sensitive BC cells, and in activating AMPK in BC and in white adipose tissue (WAT) progenitors known to cooperate to BC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 39 publications
(79 reference statements)
3
21
0
Order By: Relevance
“…The synergistic effects resulted also in increased T cell-mediated immune responses and decreased PGE2 production ( 245 ). In experimental models, we showed that aspirin or the beta-blocker agent atenolol can augment the activity of metformin, a biguanide largely employed in type 2 diabetes management and that have been associated to reduced risk of developing diverse cancers, including breast cancers (Figure 4 ), targeting both neoplastic cells and the TME ( 246 , 247 ). Metformin and phenformin affect the angiogenesis pathway ( 248 250 ) and modulate the immune response and the microbiome ( 251 , 252 ).…”
Section: Pharmacological and Immunotherapeutic Combination Targeting mentioning
confidence: 99%
“…The synergistic effects resulted also in increased T cell-mediated immune responses and decreased PGE2 production ( 245 ). In experimental models, we showed that aspirin or the beta-blocker agent atenolol can augment the activity of metformin, a biguanide largely employed in type 2 diabetes management and that have been associated to reduced risk of developing diverse cancers, including breast cancers (Figure 4 ), targeting both neoplastic cells and the TME ( 246 , 247 ). Metformin and phenformin affect the angiogenesis pathway ( 248 250 ) and modulate the immune response and the microbiome ( 251 , 252 ).…”
Section: Pharmacological and Immunotherapeutic Combination Targeting mentioning
confidence: 99%
“…This is due to the ability of Met to indirectly activate AMP-activated protein kinase (AMPK) by inhibiting oxidative phosphorylation in liver cells [ 16 ]. Recently Met class drugs have been shown to possess anticancer properties [ 17 19 ], while the mechanisms were controversial. Recent research demonstrated that Met inhibits cell growth by attenuating mitochondrial respiratory capacity, which restrains the transit of RagA-RagC GTPase heterodimer through nuclear pore complex (NPC).…”
Section: Discussionmentioning
confidence: 99%
“…Of course there are many other beta blockers in widespread clinical use, both non-selective (for example carvedilol) and selective (examples include β1-selective atenolol). While the majority of preclinical studies have focused on propranolol there is also some evidence for anticancer effects for carvedilol [ 28 , 29 ], atenolol [ 30 ] and others. These drugs vary by the degree of beta adrenergic receptor selectivity and range of off-target effects, and it remains to be seen to what extent these impact the anticancer potential of these drugs.…”
Section: Other Beta-blockersmentioning
confidence: 99%